2018
DOI: 10.1111/lang.12283
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Instruction Enhances the Effectiveness of Corrective Feedback: Variable Effects of Feedback Types and Linguistic Targets

Abstract: This study explored the impact of metacognitive instruction provided in conjunction with corrective feedback, investigating the moderating effects of two types of implicit corrective feedback (input‐providing conversational recasts vs. output‐prompting clarification requests) that targeted English third‐person singular –s and possessive determiners his/her. Adult English as a foreign language learners from intact classes (N = 83) were assigned to four conditions: metacognitive instruction plus input‐providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(67 citation statements)
references
References 92 publications
(127 reference statements)
2
65
0
Order By: Relevance
“…Second, the results indicate that peer CF does not have to be limited to grammatical structures, as was the case in most previous studies (e.g., Sato & Lyster, 2012;Sippel & Jackson, 2015). Third, the findings add to the growing body of research suggesting that metacognitive instruction can boost language acquisition in classroom environments (see Carrell, 1989;Fujii et al, 2016;Goh, 2008;Sato & Loewen, 2018;Sato, 2020). While previous studies have often focused on the impact of metacognitive instruction on listening or reading skills, this study is the first to connect metacognitive instruction to vocabulary development.…”
Section: The Impact Of Metacognitive Instruction On Peer Cfsupporting
confidence: 73%
See 1 more Smart Citation
“…Second, the results indicate that peer CF does not have to be limited to grammatical structures, as was the case in most previous studies (e.g., Sato & Lyster, 2012;Sippel & Jackson, 2015). Third, the findings add to the growing body of research suggesting that metacognitive instruction can boost language acquisition in classroom environments (see Carrell, 1989;Fujii et al, 2016;Goh, 2008;Sato & Loewen, 2018;Sato, 2020). While previous studies have often focused on the impact of metacognitive instruction on listening or reading skills, this study is the first to connect metacognitive instruction to vocabulary development.…”
Section: The Impact Of Metacognitive Instruction On Peer Cfsupporting
confidence: 73%
“…Within the field of second language acquisition, researchers have emphasized the important role of metacognition for the development of L2 reading skills (e.g., Carrell, 1989) and L2 listening skills (e.g., Goh, 2008). Recent studies have also examined metacognitive instruction in relation to grammar (Sato & Loewen, 2018) and collaborative interaction (e.g., Fujii, Ziegler, & Mackey, 2016;Sato, 2020).…”
Section: Metacognitive Instruction On Peer Feedbackmentioning
confidence: 99%
“…Yilmaz (), for example, found that higher language analytic ability facilitated learning from recasts when the focus was a salient feature (Turkish plural morpheme), whereas when recasts targeted a less salient construction (Turkish locative case marker), language analytic ability did not assist L2 learning. Although previous research has explored the effects of corrective feedback on learning linguistic constructions that differ in salience (see Sato & Loewen, ), the role of aptitude in facilitating the benefits of corrective feedback for different types of linguistic features has not received sufficient attention.…”
Section: Introductionmentioning
confidence: 99%
“…The prompt group in our study apparently failed to receive this message as strongly as the explicit recast group did, and therefore, may not have ascribed much importance to their errors. Further studies are required to examine how CF effectiveness is mediated by learners' attitude towards error correction in general, and how teachers can manipulate learners' perception of CF in a positive way (see for example, Sato & Loewen, 2018).…”
Section: ) L1mentioning
confidence: 99%